Development and preliminary evaluation of culturally specific web‐based intervention for parents of adolescents. Issue 8 (8th August 2016) - Choi, H.; Kim, S.; Ko, H.; Kim, Y.; Park, C. G.
Accessible summary: What is known on the subject?: Problematic parent–child relationships have been identified as one of the main predictors of adolescents' mental health problems, but there are few existing interventions that address this issue. The format and delivery method of existing interventions for parents are relatively inaccessible for parents with full‐time jobs and families living in rural areas. What does this paper add to existing knowledge?: The newly developed 'Stepping Stone' culturally specific web‐based intervention, which is intended to help Korean parents of adolescents to acquire both knowledge and communication and conflict management skills, was found to be feasible and well‐accepted by parents. This study enabled us to identify areas for improvement in the content and format of the intervention and strategies. This will potentially increase effect sizes for the outcome variables of parents' perception and behaviours. What are the implications for practice?: This web‐based intervention could be delivered across diverse settings, such as schools and community mental health centers, to increase parents' knowledge of adolescent's mental health and allow for early detection of mental health problems. Mental health nurses working in schools may spend a significant amount of time addressing students' mental health issues; thus, this web‐based intervention could be a useful resource to share with parents and children. In this way, the mental health nurses could facilitate parental engagement in the intervention and then help them to continue to apply and practice the knowledge and skills obtained through the program. Abstract: Introduction: There is a need for accessible, culturally specific web‐based interventions to address parent–child relationships and adolescents' mental health. Aims: This study developed and conducted a preliminary evaluation of a 4‐week web‐based intervention for parents of adolescents aged 11 to 16 years in Korea. Methods: We used a two‐group, repeated measures, quasi‐experimental study design to assess the feasibility of developing and implementing a web‐based intervention for parents. Descriptive statistics, chi‐square and t tests, and mixed effect modeling were used for data analysis. Results: The intervention and 1‐month follow‐up survey were completed by 47 parents in the intervention group and 46 parents in the attention control (AC) group. The intervention was found to be feasible and well‐accepted by parents. Discussion: This culturally specific web‐based intervention is a useful tool for knowledge dissemination among large numbers of parents. Areas for improvement in the content and format of the intervention and strategies to elicit significant parent–child interactions are provided. Implications for practice and conclusion: The intervention could be disseminated in collaboration with mental health nurses working in schools to facilitate parents' participation.